(untitled) (Annals of Medical Research, 2023)
Aim: Older adults’ populations often have insufficient vitamin D (vit-D), which may contribute to autoimmune diseases and inflammation. Few studies have examined vit-D levels and immune function in humans. The study looked at vit-D levels and inflammatory markers in older adults. Materials and Methods: Retrospective research was done. The hospital’s records were searched for the study’s data. Participants were 65-year-olds who applied to the geriatrics and internal medicine outpatient clinic between May 2020 and May 2022. Each person’s vit-D nmol/L, CRP(mg/L), lymphocyte/monocyte, neutrophil/lymphocyte, platelet/lymphocyte, ferritin, and prognostic nutritional index (PNI) levels were measured. Results: A total of 427 outpatients who applied to the geriatrics and internal medicine outpatient clinic between May 2020 and January 2022 were analyzed. Among these patients, 103 did not meet study criteria. A total of 324 participants who met the study criteria were evaluated and the participants’ mean age was 73.21±5.24 years. The mean level of vit-D found in older adults was 14.18±6.14 nmol/L. It was discovered that there was a negative correlation that was statistically significant between the individuals’ levels of vit-D and the ratio of CRP(mg/L) to MPV(fL) (p <0.05). Vit-D and PNI were found to have a correlation of r=0.205, which was found to be positive and significant (p <0.05). Logistic regression analysis was performed with vit-D level and related factors. Every 0.721 increase in PNI result in an additional unit of 25(OH) vit-D. It was found that the CRP (mg/L) variable contributed significantly to the model, and it was discovered that the presence of 1 unit of 25(OH) vit-D was increased for every 0.202 unit decrease (p <0.05). Conclusion: Insufficient vitamin 25(OH)D is found in the older adults population. 25(OH) vit-D has a negative relationship with CRP and MPV, but a positive relationship with PNI, an indicator of nutritional status. The study suggests that vit-D supplements should be provided if an older adult has adequate vit-D.